Society's Perception of Marital Rape and Its Impact on the Legal Attitudes of Muslim Women - Zanele Hope; Iwan Setiawan; Nia Paramita (Indonesian Journal of Islamic Law, 2023)
Marital rape is a form of sexual violence that is often hidden and does not receive adequate attention, both from a legal and social perspective. This research aims to examine public perceptions of marital rape and its impact on the legal attitudes of Muslim women victims in Indonesia. Using survey methods and in-depth interviews with victims, legal experts, religious leaders and the general public, this research reveals that the level of public awareness about this issue is still very low. Survey results show that 68% of respondents do not fully understand that sexual relations without consent within marriage is a form of sexual violence. In addition, cultural factors and gender-biased religious interpretations also strengthen patriarchal views. The discussion highlighted the need for comprehensive and inclusive public education, as well as collaboration with mass media and religious figures to change this negative perception. This research concludes that a holistic and integrative policy approach is needed to increase public awareness and support women victims of marital rape in seeking justice.